Extensive ro-vibrational analysis of deuterated-cyanoacetylene (DC3N) from millimeter-wavelengths to the infrared domain. (October 2020) - Melosso, Mattia; Bizzocchi, Luca; Adamczyk, Aleksandra; Canè, Elisabetta; Caselli, Paola; Colzi, Laura; Dore, Luca; Giuliano, Barbara M.; Guillemin, Jean-Claude; Martin-Drumel, Marie-Aline; Pirali, Olivier; Pietropolli Charmet, Andrea; et al.
Highlights: Combined rotational and ro-vibrational analysis of DC3 N High-resolution infrared spectra. Rotational spectra in 14 vibrational excited states. Anharmonic resonances network. Line catalog for astronomical applications. Abstract: Cyanoacetylene, the simplest cyanopolyyne, is an abundant interstellar molecule commonly observed in a vast variety of astronomical sources. Despite its importance as a potential tracer of the evolution of star-forming processes, the deuterated form of cyanoacetylene is less observed and less studied in the laboratory than the main isotopologue. Here, we report the most extensive spectroscopic characterization of DC3 N to date, from the millimeter domain to the infrared region. Rotational and ro-vibrational spectra have been recorded using millimeter-wave frequency-modulation and Fourier-transform infrared spectrometers, respectively. All the vibrational states with energy up to 1015 cm − 1 have been analyzed in a combined fit, where the effects due to anharmonic resonances have been adequately accounted for. The analysis contains over 6500 distinct transition frequencies, from which all the vibrational energies have been determined with good precision for many fundamental, overtone, and combination states. This work provides a comprehensive line catalog for astronomical observations of DC3 N.